Impact freezing of water droplet on an inclined hydrophobic surface - Neo, Min Yee (Nanyang Technological University, 2023)
The impact behaviours of freezing water droplets are experimentally studied in this project in relation to the effects of hydrophobic surface inclination. Surface inclination angle, drop release height, and cooling temperature are three variables that were varied to a set of predetermined values during the experiment. To get exact adjustments for reliable readings and analysis, an experimental setup with a goniometer and retort stand was used.